Out of exile, not out of Babylon: the diaspora theology of the Golah - Glissmann, Volker ([s.n.], 2019)
Exile and the disruptioon of the exilic period are prominent features in scholarly reconstructions of what influenced the shaping of biblical books and the development of theological thinking. The Babylonian golah community, as an exilic community, is credited by a growing number of scholars with influencing large parts of the Hebrew Bible. This study addresses the question whether the redactions show signs of an exilic mindset (first generation exiles) or are better understood as a reflection of a diaspora mindset (second/third and subsequent generations). This study also reviews all known archaeological diaspora findings from Mesopotamia in the pre-Hellenistic period (aided by insights from Elephantine) in order to build an as comprehensive as possible picture of Jewish diaspora life in Mesopotamia